Assessing the effectiveness of AFB smear versus GeneXpert MTB/RIF and real-time PCR in diagnosing tuberculosis at Hue University of Medicine and Pharmacy Hospital - Nguyễn, Hoàng Bách; Le, Thi Bao Chi; Nguyen, Thi Chau Anh; Nguyễn, Thị Khánh Linh; Phan, Văn Bảo Thắng; Trần, Thị Quỳnh Tâm; Lê, Nữ Xuân Thanh; Đinh, Thị Hải; Nguyễn, Thị Đăng Khoa; Nguyễn, Thị Tuyền; Ung, Thị Thuỷ; Nguyễn, Đức Hoàng Sang; et al. (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: Tuberculosis (TB) remains a major global health challenge, with early and accurate diagnosis being critical for effective disease control. Traditional acid-fast bacilli (AFB) smear microscopy has limited sensitivity, particularly in smear-negative cases. The advent of molecular techniques, such as the GeneXpert MTB/RIF assay and real-time PCR, has significantly improved the rapid detection of Mycobacterium tuberculosis (MTB) and rifampicin resistance. Methods: A total of 368 patients suspected of tuberculosis (TB) were analyzed using three diagnostic methods: AFB smear microscopy, GeneXpert MTB/RIF, and real-time PCR. Patient samples were collected from multiple hospital departments and categorized by demographic characteristics. AFB smear was performed using Ziehl-Neelsen staining, while GeneXpert MTB/RIF and real-time PCR were conducted following manufacturer protocols. Sensitivity, specificity, and positivity rates for each diagnostic method were compared to assess their effectiveness in detecting TB cases. Results: A prospective study at Hue University Hospital (2023-2024) compared TB diagnostic methods in 368 patients. AFB smear microscopy detected only 7.6% of cases, while GeneXpert MTB/RIF and real-time PCR identified 6.3% and 20.5%, respectively. GeneXpert demonstrated 100% sensitivity/specificity, outperforming AFB (10% sensitivity) and PCR (82.1% sensitivity, 100% specificity). Most cases were in respiratory (18.4%) and infectious disease (16.1%) departments. Conclusion: Findings highlight the critical role of molecular methods like GeneXpert and PCR in improving TB detection and urge their integration into routine screening to optimize early diagnosis and treatment.